2016
DOI: 10.1016/j.jcomm.2016.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Investment in mutually exclusive transmission projects under policy uncertainty

Abstract: In this paper we evaluate mutually exclusive transmission projects under policy and economic uncertainty. The alternatives being considered are transmission investment projects between Norway and Germany, and Norway and the UK. We apply a real option valuation framework allowing the investor to choose the optimal time and location of the investment, and also how different conditions affect the decision to invest in either of these two projects. The analysis shows that the value of the option does not necessari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…AES invests 41 billion tenge in its Kazakhstan assets in 2013-2015. "KazTransGas" has carried out capital investments in 2009 with a volume of about 245 billion tenge (Bakke et al, 2016).…”
Section: Features Of Investment In the Energymentioning
confidence: 99%
“…AES invests 41 billion tenge in its Kazakhstan assets in 2013-2015. "KazTransGas" has carried out capital investments in 2009 with a volume of about 245 billion tenge (Bakke et al, 2016).…”
Section: Features Of Investment In the Energymentioning
confidence: 99%
“…It will be used to electrolyze water to produce hydrogen. The hydrogen either returns to the grid through methods such as fuel cells or is used as energy carrier ending up in industrial or commercial application (Chen et al, 2009;Ipsakis et al, 2009;Bakke et al, 2016;Javed et al, 2020;Mayyas et al, 2020). According to the Global Energy Storage Database of the Department of Energy of the United States, as of June 2018, the world's total installed capacity of energy storage systems had reached 195.74 GW, and 1747 projects are running in operation.…”
Section: Introductionmentioning
confidence: 99%
“…They established a stochastic valuation model of energy storage in the large-scale electricity market. Bakke et al (2016) suggested considering the uncertainty of electricity price fluctuation when conducting power storage investment evaluations. The spot price of electricity generally shows strong seasonality, mean recovery, high volatility, clustering effect, and extreme price changes.…”
Section: Introductionmentioning
confidence: 99%
“…The cases in which the firm can choose among different investments, each with its own price and cost processes, are not new to the literature about investment under uncertainty. Such cases have been analyzed in the theoretical studies of Dixit (1993); Décamps et al (2006); Hagspiel et al (2016) and in applied studies dealing with real-estate Capozza and Li (1994); Geltner et al (1996), biodiesel energy Tareen et al (2000), energy for agricultural uses Lima et al (2013), and transmission cables Bakke et al (2016), to name a few. However, none of these studies have uncertainty both in the price and in the cost processes and therefore cannot study the role of correlation in the choice of the firm.…”
mentioning
confidence: 99%